Evaluation of the Dual Professional Function Transfer Program of the Cosmetology Study Program Against the Implementation of the KKNI (Indonesian National Qualification Curriculum) - Nursetiawati, Sitti; Siregar, Jenny Sista; Josua, Dian Pertiwi (Fakultas Teknik Universitas Negeri Malang, 2021)
KKNI is one of the synergies in the fields of education, training and work experience that is feasible to apply in vocational education. This study aims to evaluate, map and find out equitable competency test and certification for vocational school teachers, indicators of the success of the teacher transfer function program integrated with competency tests and certifications, and the urgency of the KKNI in the cosmetology field. The research method uses a combination of quantitative and descriptive methods with library research, which involves 42 teachers transferring the function of the cosmetology study program. Data was collected by questionnaire and analyzed a descriptive technique. The results showed that equalization of national qualifications and certification is considered very important, the need for general skills-based on KKNI for vocational school teachers, competency expertise is one of the urgent things that need to be possessed by educators. In addition, based on the results of the evaluation, it was found that the need for an effort to disseminate and distribute information about KKNI in order to increase competency for 3T regional teachers. It is necessary to support more adequate facilities and infrastructure in the process of applying competency-based vocational education and certification.